2021
DOI: 10.1038/s41598-021-99154-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between long term exposure to particulate matter and incident hypertension in Spain

Abstract: Exposure to air particulate matter has been linked with hypertension and blood pressure levels. The metabolic risks of air pollution could vary according to the specific characteristics of each area, and has not been sufficiently evaluated in Spain. We analyzed 1103 individuals, participants in a Spanish nationwide population based cohort study (di@bet.es), who were free of hypertension at baseline (2008–2010) and completed a follow-up exam of the cohort (2016–2017). Cohort participants were assigned air pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The positive associations closely align with other investigations, such as the study conducted by Viyey et al (HR = 1.48, 95% CI: 1.09-2.00), 31 the study by Zhang et al (HR = 1.04, 95% CI: 1.00-1.07), 12 and Prabhakaran et al (HR = 1.16, 95% CI: 0.95-1.43); this also showed a similar nonlinear pattern in hazard ratios within Quartiles 2-4 when utilizing a 2-year average PM2.5 measurement. 32 It is important to acknowledge the challenges associated with accurately identifying hypertension.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The positive associations closely align with other investigations, such as the study conducted by Viyey et al (HR = 1.48, 95% CI: 1.09-2.00), 31 the study by Zhang et al (HR = 1.04, 95% CI: 1.00-1.07), 12 and Prabhakaran et al (HR = 1.16, 95% CI: 0.95-1.43); this also showed a similar nonlinear pattern in hazard ratios within Quartiles 2-4 when utilizing a 2-year average PM2.5 measurement. 32 It is important to acknowledge the challenges associated with accurately identifying hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…The subgroup analysis showed that the association between PM2.5 exposure and hypertension was stronger among men, consistent with findings from other studies. 2,31 This discrepancy could be attributed to the differing duties of male and female officers. Female personnel often hold administrative or medical positions with less outdoor exposure and operational activity than their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of American women, long-term exposure to PM 2.5 was prospectively associated with hypertension risk (HR, 1.06 [95% CI:, .02–1.11]). 48 Likewise, in Spanish adults, higher exposure to PM 2.5 and PM 10 was significantly related to an increased incidence of hypertension 49 and similar in cohorts of Chinese children and adolescents 50 and adults. 51 In a Chinese cohort exposed to extreme levels of air pollution, a relationship between black carbon (an anthropogenic surrogate of fossil fuel combustion) and ambulatory blood pressure was demonstrated: a 1 µg increase in black carbon during the previous 10 hours was associated with an increase in systolic blood pressure of 0.53 mm Hg and diastolic blood pressure of 0.37 mm Hg (95% CI, 0.17–0.89 and 0.10–0.65 mm Hg, respectively), 52 which also caused heart rate variability suggestive of sympathetic dominance.…”
Section: Recent Epidemiological/observational Evidence For Adverse Ef...mentioning
confidence: 70%
“…(Mean ± SD of PM 2.5 exposure: 15.61 ± 4.24 µg/m 3 vs. 53.4 ± 23.0 µg/m 3 ). Another cohort study conducted in a Spanish population showed that the Mediterranean diet did not modify the relation between long-term exposure to PM 2.5 and incident of HTN [ 24 ]. However, the sample size of this study ( n= 1,103) was small, and the PM 2.5 exposure levels of subjects were much lower than those of our subjects.…”
Section: Discussionmentioning
confidence: 99%